Serum HDL-C levels in children with epilepsy: a single-center retrospective study - Guo, Hong-Li; Dong, Na; Hu, Ya-Hui; Qiu, Jin-Chun; Jiang, Zhen-Zhou; Liu, Qian-Qi; Lu, Xiao-Peng; Chen, Feng (Frontiers in Nutrition, 2025)
PurposeThis study aims to compare the difference in serum high-density lipoprotein cholesterol (HDL-C) levels between children with epilepsy and healthy children and to assess its potential influencing factors.MethodsFor comparison, we retrospectively collected data on 1,002 children with epilepsy who visited the Department of Neurology at the Children’s Hospital of Nanjing Medical University. Additionally, we included 127 healthy children who underwent routine health examinations at our hospital’s Health Examination Center. This study also incorporated 98 recently diagnosed epilepsy patients who had not yet received treatment with anti-seizure medications (ASMs) as a source of baseline data. Demographic information and laboratory test results were retrieved from the hospital information system. The Kolmogorov–Smirnov test, the Mann–Whitney test, the Fisher’s exact test, odds ratios (OR), Spearman or Pearson correlation coefficients, and post-hoc analysis were used to conduct statistical analysis.ResultsHealthy children exhibited significantly higher serum levels of HDL-C compared to children with epilepsy and the baseline values. Notably, a higher percentage of children with epilepsy exhibited a low HDL-C levels (<1.0 mmol/L) compared to healthy children, showing an increased risk of dyslipidemia (OR, 2.773; 95% CI, 0.9879–7.457). The type of ASMs had a notable effect on serum HDL-C levels, particularly with hepatic enzyme-inducing ASMs like oxcarbazepine, which significantly raised the serum HDL-C levels. The serum HDL-C levels were also associated with factors such as age, epilepsy history, and brain magnetic resonance imaging findings. Additionally, there was a weak negative association between serum vitamin D levels and serum HDL-C levels (R = -0.37, p = 0.0014). Moreover, children who received vitamin D supplementation demonstrated a higher level of HDL-C than those without such supplementation.ConclusionSerum HDL-C levels are notably lower in children with epilepsy than in healthy children. Treatment with ASMs can partially increase the serum HDL-C levels, potentially approaching those found in healthy children. Therefore, the decrease in serum HDL-C levels in children with epilepsy irrespective of receiving ASMs treatment should warrant ongoing attention.